2021
DOI: 10.3389/fdata.2021.750536
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analysis of the US Drought Monitor Maps With Machine Learning and Multiple Drought Indicators

Abstract: The US Drought Monitor (USDM) is a hallmark in real time drought monitoring and assessment as it was developed by multiple agencies to provide an accurate and timely assessment of drought conditions in the US on a weekly basis. The map is built based on multiple physical indicators as well as reported observations from local contributors before human analysts combine the information and produce the drought map using their best judgement. Since human subjectivity is included in the production of the USDM maps, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Following previous studies (Sun Yu et al, 2020;Shah et al, 2021;Tan et al, 2021), four dominant factors, namely normalized difference vegetation index (P_NDVI), land surface temperature (P_LST), shape index (P_SI) and area (P_Area) of UGS patches were selected to explore their influence on the cooling intensity and range of UGS. The shape index represents the complexity of patch shape.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Following previous studies (Sun Yu et al, 2020;Shah et al, 2021;Tan et al, 2021), four dominant factors, namely normalized difference vegetation index (P_NDVI), land surface temperature (P_LST), shape index (P_SI) and area (P_Area) of UGS patches were selected to explore their influence on the cooling intensity and range of UGS. The shape index represents the complexity of patch shape.…”
Section: Discussionmentioning
confidence: 99%
“…found that the TVoE was about 0.6-0.62 ha in Hong Kong, Jakarta, Mumbai, and Singapore, and 0.92-0.96 ha in Kaohsiung, Kuala Lumpur, and Taiwan. Tan et al (2021) found that the TVoE of three-based green spaces was about 0.31 ha in Nanning, China. The TVoE was found to be 4.55 ha in Fuzhou (Yu, et al, 2017).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations